Testing the circulation of expanded flaps—prevention of necrosis of expanded flaps (a clinic study) - Han, Tao; Chen, Haini; Chen, Jianbin; Cui, Jie; Shen, Weimin (Frontiers in Pediatrics, 2023)
Background: Expanded flaps are commonly used in plastic surgery. Although expanded flaps are more resistant to hypoxia than unexpanded flaps, flap necrosis can sometimes occur, particularly with skin incisions of regular proportion. Distal skin necrosis of expansion flap can be avoided by careful design; however, the utilization rate of expansion flap decreases. Consequently, successfully avoiding distal skin flap necrosis remains a challenge. In this study, we designed a device for testing the circulation of the expanded flap that can decrease the risk of expanded flap necrosis, thus maximizing the use of expanded flap Methods: A total of 128 patients who underwent surgical repair between 2011 and 2019 and were retrospectively examined with the device for testing the circulation of the expanded flap were included in the study. The procedure included: (1) making a device for testing the circulation; (2) implanting a skin expander; (3) injecting normal saline into skin expander; (4) testing the circulation of the expanded flap; (5) transferring expanded flap to repair the defect. Results: One hundred forty-eight expanded flaps were implanted in 128 patients. The expanded flap that was transferred to repair the defect had no necrosis and infection. None of the expanded flaps with separated blood supply, which could be observed during operations, revealed complications. The survival rates of the expanded flap were increased through testing the circulation of the expanded flap. Expanded flaps designed by this method showed no swelling or paleness and no obvious temperature changes. In addition, the ratio of length to width could be extended to 3:1. Conclusions: Our proposed method resulted as an effective surgical procedure for the repair of tissue defects. This approach could effectively change the direction of the blood vessel of the expanded skin flap and prevent necrosis of expanded flaps, thus representing a practical way to increase the use of expanded flaps as well as the flap survival rate, making the whole expanded flap transfer procedure more convenient.